AP-1 (bZIP) Transcription Factors as Potential Regulators of Metallothionein Gene Expression in Tetrahymena thermophila - de Francisco, Patricia; Amaro, Francisco; Martín-González, Ana; Gutiérrez, Juan Carlos (Frontiers in Genetics, 2018)
Metallothioneins (MT) are multi-stress proteins mainly involved in metal detoxification. MT gene expression is normally induced by a broad variety of stimulus and its gene expression regulation mainly occurs at a transcriptional level. Conserved motifs in the Tetrahymena thermophila MT promoters have been described. These motifs show a consensus sequence very similar to AP-1 sites, and bZIP type transcription factors might participate in the MT gene expression regulation. In this research work, we characterize four AP-1 transcription factors in each of four different analyzed Tetrahymena species, detecting a high conservation among them. Each AP-1 molecule has its counterpart in the other three Tetrahymena species. A comparative qRT-PCR analysis of these AP-1 genes have been carried out in different T. thermophila strains (including metal-adapted, knockout and/or knockdown strains among others), and under different metal-stress conditions (1 or 24 h Cd2+, Cu2+, or Pb2+ treatments). The possible interaction of these transcription factors with the conserved AP-1 motifs present in MT promoters has been corroborated by protein-DNA interaction experiments. Certain connection between the expression patterns of the bZIP and MT genes seems to exist. For the first time, and based on our findings, a possible gene expression regulation model including both AP-1 transcription factors and MT genes from the ciliate T. thermophila has been elaborated.